Analysis of Rice Farming Income in Jogopaten Village, Buluspesantren District, Kebumen Regency - Hutami, Etika Dwi; Santoso, Siswanto Imam; Handayani, Migie (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
This study aims to analyze the correlation between land area, seeds, fertilizers, pesticides, and labor with rice farming income in Jogopaten Village, Buluspesantren District, Kebumen Regency. The research was conducted from January to February 2022, in Jogopaten Village. The location selection was done purposively. The method used was a survey method. Sampling was done by simple random sampling, namely rice farmers as many as 60 respondents. The data analysis method used was quantitative descriptive analysis with the calculation of production costs, revenues, income, and pearson correlation analysis. Based on the results of the study, the variables of land area, seeds, fertilizers, and pesticides have a positive and significant correlation with farmers' income, while the variable days of work (HOK) have a negative and significant correlation with income. Variables of land area, fertilizers, and pesticides have a very strong correlation with income. Pearson correlation value between the land area variable and income is 0.994, so the two variables have a very strong correlation. Pearson correlation value between the fertilizer variable and income is 0.986, so it has a very strong correlation. Pearson correlation value between pesticide variable and income is 0.907, so it has a very strong correlation. The seed variable has a low correlation with income, this is evidenced by the low pearson correlation value of 0.356. The variable day of work (HOK) has a very low correlation with income, this is evidenced by the very low pearson correlation value (-0.151).